Rural and urban patterns of severe injuries and hospital mortality in Australia: An analysis of the Australia New Zealand Trauma Registry: 2015–2019. Issue 6 (June 2022) - Heathcote, Katharine; Devlin, Anna; McKie, Emily; Cameron, Peter; Earnest, Arul; Morgan, Geoff; Gardiner, Ben; Campbell, Don; Wullschleger, Martin; Warren, Jacelle
Highlights: Information about geographical variations on severe trauma occurrence and outcomes in Australia is sparse, despite data showing that people injured in rural areas are in poorer health and at greater risk of serious injuries. Analyses of the Australian Trauma Registry showed that, compared to major cities, rural patients were younger, more likely to have spinal cord injuries, and sustain traffic-related injuries that are 'off road'. Excess mortality risk in rural areas, compared to major cities was evident for patients sustaining severe traumatic brain injury (TBI) spinal cord injury (SCI) and head trauma in addition to those with intentional injuries. The Australian Trauma Registry captures only about 15% of all comparable injury deaths in major cities, and, respectively 8% and 4% of deaths in regional and remote areas. To inform prevention strategies and reduce morbidity and mortality associated with rural trauma, data linkage systems are required, that include information about patient care from pre-hospital providers, regional hospitals and major trauma. Abstract: Introduction: In Australia, people living in rural areas, compared to major cities are at greater risk of poor health. There is much evidence of preventable disparities in trauma outcomes, however research quantifying geographic variations in injuries, pathways to specialised care and patient outcomes is scarce. Aims: (i) To analyse the Australia New Zealand Trauma Registry (ATR) data and report patterns of serious injuries according to rurality of the injury location ii) to examine the relationship between rurality and hospital mortality and iii) to compare ATR death rates with all deaths from similar causes, Australia-wide. Method: A retrospective cohort study of patients in the ATR from 1 st July 2015 to 30 th June 2019 was conducted. Descriptive analyses of trauma variables according to rurality was performed. Logistic regression quantified the moderating effect of rurality on trauma variables and hospital mortality. Australian death data on similar injuries were sourced to quantify the additional mortality attributable to severe injury occurring outside Major Trauma Centres (MTCs). Results: Compared to major cities, rural patients were younger, more likely to have spinal cord injuries, and sustain traffic-related injuries that are 'off road'. Injuries occurring outside people's homes are more likely. Mortality risk was greater for patients sustaining severe traumatic brain injury (TBI) spinal cord injury (SCI) and head trauma in addition to intentional injuries. Compared to the ATR data, Australian population-wide trauma mortality rates showed diverging trends according to rurality. The ATR only captures 14.1% of all injury deaths occurring in major cities and, respectively, 6.3% and 3.2% of deaths in regional and remote areas. Conclusion: Compared to major cities, injuries occurring in rural areas of Australia often involve different mechanisms and result in different types of severe injuries. Patients with neurotrauma and intentional injuries who survived to receive definitive care at a MTC were at higher risk of hospital death. To inform prevention strategies and reduce morbidity and mortality associated with rural trauma, improvements to data systems are required that involve data linkage and include information about patient care from pre-hospital providers, regional hospitals and major trauma centres.